Obstructive Sleep Apnea Syndrome (OSAS) and Cardiovascular System - Lombardi, Carolina; Tobaldini, Eleonora; Montano, Nicola; Losurdo, Anna; Parati, Gianfranco (La Medicina del Lavoro, 2017)
There is increasing evidence of a relationship between Obstructive Sleep Apnea (OSA) and cardiovascular diseases. The strong association between OSA and arterial hypertension, in particular in patients with resistant hypertension and/or a non-dipping profile, has been extensively reported. The relationship between OSA and high blood pressure (BP) has been found independent from a number of confounders, but several factors may affect this relationship, including age and sex. It is thus important to better assess pathophysiologic and clinical interactions between OSA and arterial hypertension, also aimed at optimizing treatment approaches in OSA and hypertensive patients with co-morbidities. Among possible mechanisms, cardiovascular autonomic control alterations, altered mechanics of ventilation, inflammation, endothelial dysfunction, and renin–angiotensin–aldosterone system should be considered with particular attention. Additionally, available studies also support the occurrence of a bidirectional association between OSA and cardiovascular alterations, in particular heart failure, stroke and cardiac arrhythmias, emphasizing that greater attention is needed to both identify and treat sleep apneas in patients with cardiovascular diseases. However, a number of aspects of such a relationship are still to be clarified, in particular with regard to gender differences, effect of sleep-related breathing disorders in childhood, and influence of OSA treatment on cardiovascular risk, and they may represent important targets for future studies.